한반도 지역 SBAS 대류층 지연 보정 모델의 정확도 검증 - 김동욱; 한덕화; 기창돈; 이철수; 이충희; Kim, Dong-uk; Han, Deok-hwa; Kee, Chang-don; Lee, Chul-soo; Lee, Choong-hee (한국항행학회논문지, 2016)
In this paper, we verified accuracy of the satellite based augmentation system (SBAS) tropospheric delay correction model for the Korean region. We employed the precise data of the tropospheric zenith path delay (ZPD) which is provided by the international GNSS service (IGS). In addition, we compared the verification results with that of the Saastamoinen model and the Hopfield model. Consequently, the bias residual error of the SBAS tropospheric delay correction model is about 50 mm, whereas the Saastamoinen model and the Hopfield model are more accurate. This residual error by the tropospheric delay model can affect the SBAS user position accuracy, but there is no problem in SBAS accuracy requirement. If we modified the meteorological parameters for SBAS tropospheric model to appropriate in Korean weather environment, we can provide better SBAS service to the Korean user. 본 논문에서는 한반도 지역에서 SBAS (satellite based augmentation system) 대류층 지연 보정 모델의 정확도 성능을 검증하였다. 정확도 분석을 위한 대류층 지연량 참값으로 IGS (International GNSS Service)에서 제공하는 정밀 대류층 천정 지연량인 ZPD(zenith path delay) 데이터를 활용하였다. 그리고 대표적인 대류층 지연 모델인 Saastamoinen 모델 및 Hopfield 모델과 성능을 비교하였다. 그 결과 SBAS 대류층 지연 보정 모델의 잔여 오차는 약 50 mm 수준으로, Saastamoinen 모델 및 Hopfield 모델보다 성능이 떨어졌다. 이 대류층 지연 모델에 의한 잔여오차는 SBAS 정확도 요구조건에는 문제가 없지만, 사용자 측위 성능에는 영향을 미칠 수 있다. 만약 한반도 기상 환경에 적합하도록 SBAS 대류층 보정 모델의 기상 파라미터를 수정한다면, 더 좋은 성능의 SBAS 서비스를 한반도에 제공할 수 있을 것으로 기대된다.